EFEKTIVITAS PEMANFAATAN ECOBRICK SEBAGAI MEDIA PEMBELAJARAN PADA MATERI DAUR ULANG SAMPAH PLASTIK DI KELAS 3 SEKOLAH DASAR - Intan Anggraini; Yasir Arafat; Susanti Faipri Selegi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
PPKn learning in elementary schools still uses the lecture method and lack of student motivation towards learning and lack of utilizing learning media by resulting in students becoming less active in the classroom. The purpose of this study is to determine the effectiveness of using ecobrick as a learning medium for recycling plastic waste in grade 3 elementary schools. This type of research is pre-experimental designs and uses One Group Pretest-Posttest Research Design consisting of two classes, namely classes 3.A and 3.C. The population is 33 students and a sample of 33 students. Data analysis techniques are descriptive statistics and inferential data analysts. Based on the results of the Pretest, the average score of student learning outcomes is 69.21 with a good category, it can be concluded that the level of ability of student learning outcomes in understanding the test and mastery of PPKn material before using ecobrick learning media is good. As for the average after.